STUDENTS’ PERCEPTION OF THE USE OF YOUTUBE IN TRANSLATION CLASS - Yofri Karisi; Noldy Pelenkahu; Mister Gidion Maru (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2021)
This research aimed to describe students’ perception of the use of YouTube in English translation classes. In conducting this research, the researcher used a questionnaire and the result was presented descriptively. The researcher analyzed the data according to three indicators such as accuracy, acceptability, and readability. Accuracy refers to whether the meaning of the source language is similar to the target language. The term acceptability refers to whether or not the translation has been revealed according to the target language rules, norms, or cultures. The readability deals with how natural and easy a translation can be read by the target readers. For the first indicator's accuracy, according to data analysis, it can be analyzed that the students choose 60% agree, 20% strongly agree, 17% choose neutral and 3% disagree. For the second indicator acceptability, 56% Agree, 27% Strongly agree, 16% neutral and 1% disagree. For the last indicator readability, 56 % agree, 30% strongly agree, 13% neutral and 1% choose to disagree. Based on this research, the researcher concluded that students’ perception of the use of youtube in English translation class was needed to help them understand the translation and learning process.